Securing Durable Development in Afghanistan : Policy Notes for the Government - World Bank (Washington, DC, 2013)
The government of Afghanistan has an opportunity in the coming months to turn the country around. It is now opportune to improve security, governance, and development. Unprecedented international military support, political attention and aid are available to Afghanistan. The government is inheriting years of good economic performance, notable progress on social outcomes, and continuing strong support from the international community. Gross domestic product (GDP) has grown at an average of 12 percent in the last five years with moderate inflation and a stable Afghani. The National Solidarity Program is spurring community-driven rural development in nearly all districts of the country and the large opium economy is in retreat. Significant progress has been achieved in basic education and health. Gender indicators are improving. The government and its development partners have an obligation to seize this opportunity for all Afghans. All donors made an explicit commitment at the London Conference in January 2010 to progressively cede leadership to the Afghan people. The donors agreed to route half of their development aid through the national budget from the current one-fifth in the next two years, as local capacity to execute development programs improves. Further, donors aim to work together to improve aid effectiveness by better alignment with Afghan priorities, minimize opportunities for corruption and improve aid predictability. This overview summarizes the view of the World Bank on priority development issues and policy actions. It is intended to be a useful reference for the government as it prepares for the Kabul conference. The issues and policy options proposed are consistent with the ands and the Bank's interim strategy note of May 2009. It synthesizes the key findings and analyses of the detailed policy notes which draw upon the World Bank's past and ongoing work in Afghanistan, as well as wider experiences, including those from other countries experiencing conflict.